Analisa Model Directed Diffusion (DD) Berbasis Cluster Pada Wireless Sensor Network (WSN) - Sahid Ridho; Indra Yasri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Limitations of energy is one of the important issues in the network sensor network (WSN). The energy used for data transmission between sensor nodes. one method to solve this problem is to choose the proper protocol. Many researchers have proposed protocols are energy efficient and have a good data collection mechanisms. One well-known protocol used is directed diffusion (DD). DD is a data centric protocol that also focus in energy efficiency and have a good data collection capabilities. DD good protocol but there are still some weaknesses were found in DD. DD on the implementation flooding (flooding) a request message to a network of sensors and then draw the appropriate message and flooding the request message to the network node number will increase energy usage and network traffic. Cluster or grouping of nodes one way to hold back flooding overhead. Proposed research directed diffusion-based cluster showed increased energy efficiency and reduce traffic congestion in the network of sensors. Based on the results of the analysis suggest that, over the J-Sim simulation showed that directed diffusion-based cluster is able to limit and control the flooding overhead to determine the number of nodes in each cluster efficiently.Keywords : Wireless Sensor Networks, Directed diffusion, cluster, J-Sim